From low to high inflation: Implications for emerging market and developing economies - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge (Koç University-TÜSIAD Economic Research Forum (ERF), 2022)
Recent energy and food price surges, in the wake of Russia's invasion of Ukraine, have exacerbated inflation pressuresthat are unusually high by the standards of the past two decades. High and rising inflation has prompted many emerging market and developing economy (EMDE) central banks and some advanced-economy central banks to increase interest rates. Inflation is expected to ease back towards targets over the medium-term as recent shocks unwind, but the 1970s experience is a reminder of the material risks to this outlook. As inflation remains elevated, the risk is growing that, to bring inflation back to target, advanced economies need to undertake a much more forceful monetary policy response than currently anticipated. If this risk materializes, it would imply additional increases in borrowing costs for EMDEs, which are already struggling to cope with elevated inflation at home before the recovery from the pandemic is complete. EMDEs need to focus on calibrating their policies with macroeconomic stability in mind, communicating their plans clearly, and preserving and building their credibility.
Keywords: E31; E32; E37; Q43; 330; Global Inflation; Commodity Price; War in Ukraine; Global Recession; Great Inflation; Monetary Policy Tightening